Exports and olympic games: Is there a signal effect? - Wolfgang Maennig; Felix Richter (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2012)
Rose & Spiegel (2011) find that Olympic Games host countries experience significant positive, lasting effects on exports. They interpret their results as an indication that countries use the hosting of such events to signal openness and competitiveness. We challenge these empirical findings on the grounds that a comparison of structurally different and non-matching groups of countries might suffer from a selection bias. We demonstrate that with an appropriate matching and treatment methodology, the significant Olympic effect disappears.
Keywords: F1; L83; 330; export; Olympic Games; international trade; treatment; matching